Sexo, dinheiro e repressão: o global e o local na dinâmica sócio-espacial da prostituição - Silva, Roberto Florentino da (2013)
This dissertation seeks to analyze the socio-spatial dynamics of prostitution in the city of Francisco Beltrão, Paraná, in its earliest manifestations, in specific moments, and at present, at another time, and alterations in the forms, functions, structures and processes of this activity, here understood as an economic activity. Part of the overall scale of the sex industry in a globalized world, of international trafficking of people, and the forms of organization of this activity in the city of São Paulo, to give a more precise cut of this activity on the scale of Francisco Beltrão. It attempts to analyze the explosive mix of sex, money and prejudices just as a socioeconomic activity in the light of the categories of Economic Geography.